2011
DOI: 10.1055/s-0031-1271380
|View full text |Cite
|
Sign up to set email alerts
|

Offen chirurgische versus laparoskopische Versorgung der iatrogenen Kolonperforation - Ergebnisse nach 13 Jahren Erfahrungen

Abstract: An iatrogenic colon perforation mostly leeds to the immediate indication for a surgical treatment. The morbidity and mortality is -primarily determined through the appearance of postoperative complications due to delays in diagnostics and treatment. In this study the feasibility of a laparoscopic treatment could be shown. The laparoscopy with its minimal access trauma offers an enlargement of the diagnostics as well as a safe treatment of the perforation in most patients. However, the laparoscopic treatment es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 25 publications
0
17
0
2
Order By: Relevance
“…The authors found fewer complications and a shorter length of hospital stay for the patients in the laparoscopic group [ 110 ]. Other studies by Rothold et al [ 125 ] and Schloricke et al [ 127 ] also observed fewer postoperative complications and significantly shorter hospital stays when utilizing the laparoscopic approach. Similar studies with similar results were published by Coimbra et al [ 124 ] and Kim et al [ 128 ], although in these studies, delayed surgeries (> 24 h) and ostomy formation rates were more frequently observed in the open groups, with higher primary repair rates in the laparoscopic groups.…”
Section: Resultsmentioning
confidence: 80%
“…The authors found fewer complications and a shorter length of hospital stay for the patients in the laparoscopic group [ 110 ]. Other studies by Rothold et al [ 125 ] and Schloricke et al [ 127 ] also observed fewer postoperative complications and significantly shorter hospital stays when utilizing the laparoscopic approach. Similar studies with similar results were published by Coimbra et al [ 124 ] and Kim et al [ 128 ], although in these studies, delayed surgeries (> 24 h) and ostomy formation rates were more frequently observed in the open groups, with higher primary repair rates in the laparoscopic groups.…”
Section: Resultsmentioning
confidence: 80%
“…Four studies were performed in single centers [ 26 , 37 39 ], whereas 2 were bi-centric studies [ 25 , 40 ]. Two studies were conducted in Asia [ 37 , 39 ], two in Europe [ 25 , 38 ], and two in North America [ 26 , 40 ]. Overall, they analyzed a total of 161 patients undergoing laparoscopic or open surgeries for ICP treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to other methods, such as the open low anterior resection of the rectum, there is a significant discrepancy between the size of the surgical wound and the surgical specimen that is removed during the operation [ 8 , 9 ]. Hence, laparoscopic pancreatic surgery could lead to a reduced intraoperative dysregulation of catecholamines or a reduced compromise of the immune system.…”
Section: Discussionmentioning
confidence: 99%